Scale economies and the dynamics of recurring auctions - Thomas D. Jeitschko; Elmar Wolfstetter (Humboldt University of Berlin, Interdisciplinary Research Project 373: Quantification and Simulation of Economic Processes, 1998)
We analyze the dynamics of a game of sequential bidding in the presence of stochastic scale effects in the form of stochastic economies or diseconomies of scale. We show that economies give rise to declining expected equilibrium prices, whereas the converse is not generally true. Moreover, first- and second-price auctions are not always revenue equivalent. Indeed, economies of scale make the second-price format more profitable for the seller, whereas revenue equivalence holds in the case of diseconomies.
urn:nbn:de:kobv:11-10060022
Keywords: D44; 330; auctions; procurements; sequential auctions; economies of scale